PEMBUATAN MINUMAN SEDUH FUNGSIONAL DARI BIOAKTIF POD HUSK KAKAO - Gatot Siswo Hutomo,Rostiati Dg Rahmatu, Yudi Setiawan (AGROTEKBIS, 2016)
The purpose of the research was to determine the antioxidant activity of beverage made from various weights of cocoa pod husk extracts and to identify panelist responses on sensory characteristics of the beverage. The research used a Completely Randomized Design (CRD) with treatments consisting of 5 g, 10g, 15 g, and 20 g of cocoa pod husk extracts. The extracts were then concentrated by adding maltodextrin (2 g) and sucrose (1 g). Highest content of total galat acid fenol (146.57 mg) and ascorbic antioxidant (1535.21 mg) which is equal to the total fenol and antioxidant contained in tea. Organoleptic test showed that the panelists like the beverage made from the 20 g cocoa pod husk, therefore, this treatment will be used to manufacture the beverage.